The tumour suppressor protein VHL targets hypoxia-inducible factors for oxygen-dependent proteolysis. - Maxwell, P; Wiesener, MS; Chang, G; Clifford, S; Vaux, E; Cockman, M; Wykoff, C; Pugh, C; Maher, E; Ratcliffe, P (1999)
Hypoxia-inducible factor-1 (HIF-1) has a key role in cellular responses to hypoxia, including the regulation of genes involved in energy metabolism, angiogenesis and apoptosis. The alpha subunits of HIF are rapidly degraded by the proteasome under normal conditions, but are stabilized by hypoxia. Cobaltous ions or iron chelators mimic hypoxia, indicating that the stimuli may interact through effects on a ferroprotein oxygen sensor. Here we demonstrate a critical role for the von Hippel-Lindau (VHL) tumour suppressor gene product pVHL in HIF-1 regulation. In VHL-defective cells, HIF alpha-subunits are constitutively stabilized and HIF-1 is activated. Re-expression of pVHL restored oxygen-dependent instability. pVHL and HIF alpha-subunits co-immunoprecipitate, and pVHL is present in the hypoxic HIF-1 DNA-binding complex. In cells exposed to iron chelation or cobaltous ions, HIF-1 is dissociated from pVHL. These findings indicate that the interaction between HIF-1 and pVHL is iron dependent, and that it is necessary for the oxygen-dependent degradation of HIF alpha-subunits. Thus, constitutive HIF-1 activation may underlie the angiogenic phenotype of VHL-associated tumours. The pVHL/HIF-1 interaction provides a new focus for understanding cellular oxygen sensing.